2012
DOI: 10.1002/eqe.2182
|View full text |Cite
|
Sign up to set email alerts
|

The cause of unproportionately large higher mode contributions in the inelastic seismic responses of high‐rise core‐wall buildings

Abstract: SUMMARY In the conventional seismic design of high‐rise reinforced concrete core‐wall buildings, the design demands such as design shear and bending moment in the core wall are typically determined by the response spectrum analysis procedure, and a plastic hinge is allowed to form at the wall base to limit the seismic demands. In this study, it is demonstrated by using a 40‐story core‐wall building that this conventional approach could lead to an unsafe design where the true demands—the maximum inelastic seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
4
39
0
1
Order By: Relevance
“…21 that the seismic shear demands of W2 from NLRHA procedure are about 2 times as high as the corresponding shear demands from RSA procedure and that their distribution patterns throughout entire height are almost the same. These results agree quite well with the results of Klemencic et al [7], and Munir and Warnitchai [9]. Similarly, the bending moment from NLRHA is also about 2 times the corresponding demands from RSA procedure throughout the entire height of the building as depicted in Fig.…”
Section: Verification Of Rsa Proceduressupporting
confidence: 90%
See 2 more Smart Citations
“…21 that the seismic shear demands of W2 from NLRHA procedure are about 2 times as high as the corresponding shear demands from RSA procedure and that their distribution patterns throughout entire height are almost the same. These results agree quite well with the results of Klemencic et al [7], and Munir and Warnitchai [9]. Similarly, the bending moment from NLRHA is also about 2 times the corresponding demands from RSA procedure throughout the entire height of the building as depicted in Fig.…”
Section: Verification Of Rsa Proceduressupporting
confidence: 90%
“…In MMS method, the elastic seismic shear demand is reduced by a seismic modification factor only in the first vibration mode and then combined with the elastic shear demand of other higher modes into total response. Munir and Warnitchai [9] used a method called uncoupled modal response history analysis (UMRHA) adapted from Chopra and Goel [23] to decompose the inelastic seismic responses into the contribution of each vibration modes. The results are compared with the demands from RSA procedure (with R=1 and R=5.5) and they found that the demands from UMRHA matched RSA (R=5.5) only in the first mode and reasonably close to RSA (R=1) in other higher modes.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure requires to perform the multimode pushover analysis of an inelastic structural model and, therefore, can also be viewed as a simplification of the modal pushover analysis (MPA) proposed by Chopra and Goel. [13] More recently, Ahmed and Warnitchai [14] and Mehmood et al [15,16] applied the uncoupled modal response history analysis (UMRHA)…”
Section: Background and Motivationmentioning
confidence: 99%
“…The design forces in this method are obtained by using a single response modification factor (R) for all modes of response to reduce the elastic forces computed by RSA procedure. However, previous researchers have found that flexural yielding at the base region of the wall reduced mainly the first-mode shear but higher-mode shears were not significantly affected by inelastic action [2][3][4][5]. Most studies were based on comparing results from RSA procedure to the 'referenced' results from nonlinear response history analysis (NLRHA), which is considered as the most accurate method available to compute design forces of a structural system subjected to earthquake loading.…”
Section: Introductionmentioning
confidence: 99%